CMET-33. PHASE II STUDY OF PALBOCICLIB IN BRAIN METASTASES HARBORING CDK PATHWAY ALTERATIONS. (11th November 2019) - Brastianos, Priscilla; Cohen, Justine; Wang, Nancy; Lee, Eudocia; Ligibel, Jennifer; Chukwueke, Ugonma; Keeley, Maura; Oh, Kevin; White, Michael; Gerstner, Elizabeth; Batchelor, Tracy; Lawrence, Donald; et al.
Abstract: BACKGROUND: Up to 25% of all cancer patients will develop brain metastases and prognosis remains poor. In preclinical work, we discovered that more than 50% brain metastases genomically diverge from primary tumors and harbor alterations in genes involved with cell cycle regulation. We thus initiated a phase II study to evaluate the efficacy and safety of the cyclin dependent kinase (CDK) 4/6 inhibitor, palbociclib, in patients with recurrent brain metastases with alterations in the CDK pathway (NCT02896335). METHODS: The primary endpoint of the trial is the rate of intracranial benefit (defined as CR, PR, or SD, per RANO) at 8 weeks after the start of palbociclib. A Simon two-stage design was used to compare the rate of intracranial benefit for a null rate of 10% against an alternative of 30%. Fifteen patients were to be enrolled in the first stage. If fewer than 2 responders were observed, then the study would stop for insufficient evidence of efficacy. If 6 or more responders were observed among the total of 30, this treatment regimen would be considered worthy of further study. CSF, blood samples and tumor samples were collected to elucidate the genomic determinants of response to CDK inhibitors in the brain. RESULTS: A total of 14 patients have been accrued (5 with breast cancer, 4 with melanoma, 3 esophageal and 2 with non-small cell lung cancer) thus far. One or more grade-3 or higher adverse events at least possibly related to treatment were seen in six (42%) patients, the majority being hematologic toxicities. At the time of the data analysis, eight (57%) patients had achieved intracranial benefit. Therefore, the study met primary endpoint. CONCLUSIONS: In this unique, genomically-guided brain metastasis trial, we demonstrate that the CDK 4/6 inhibitor, palbociclib, is well-tolerated and has activity in patients with brain metastases.